Polarization of Λ hyperons produced inclusively in v p and Mathematical expressionp charged current interactions - Jones, G; Kennedy, B; O'Neale, S; Böckmann, K; Gebel, W; Geich-Gimbel, C; Nellen, B; Cooper-Sarkar, A; Grant, A; Klein, H; Morrison, D; Schmid, P; et al. (Springer-Verlag, 1985)
Lambda hyperons from v p and Mathematical expressionp charged current interactions have been analysed for polarization. A significant polarization is observed for Λ particles in the quasi-elastic region for both types of interactions. Part of this polarization is due to the decay of highly polarized Σ(1385) resonances. The results are compared with simple predictions of the quark parton model. © 1985 Springer-Verlag.